ASEAN-Korea commemorative summit 2014 : towards an "Asian community"? - Yoon, Sukjoon (2015)
ASEAN and South Korea recently held a summit to mark 25 years of partnership. President Park Geun-hye spoke confidently of ASEAN and South Korea working together to build a multilateral "Asian Community".